What do measures of ‘oral health-related quality of life’ measure? - Locker D, Allen F. (Blackwell Synergy, 2007)
The terms ‘health-related quality of life’ and ‘quality of life’ are now in common use to describe the outcomes of oral health conditions and therapy for those conditions.